Quality administration and management in higher education in Nigeria : implications for human resource development. - Akinyemi, Gbenga M.; Zainal Abiddin, Norhasni (Canadian Center of Science and Education, 2013)
The dynamic changes in today’s world have made countries of the world masters of their own destinies. In this light, it has become noted today that ‘the affluence or penury of nations depends largely on the quality of higher education’. This is informed by the fact that higher education systems of a nation is the ‘machinery of manpower creation’ of the nation and as a result nations have to embrace quality on a continuous basis to be able to be in touch with the realities of today’s change in technological, sociological and economical dimensions. Quality higher education system will produce quality skills and quality human capacity. Therefore, in adjustment to needs for development countries such as Nigeria should embrace and implement Continuous Quality Improvement (CQI), Total Quality Management (TQM) in the universities and Higher Education administration for the purpose of all-round Human Resource Development. TQM and CQI implementation in the university system will go a long way in expanding the skills and capacity of the academic staffs and consequently that of the students. In effect, there will be increase in Human Capital Development across the nation and the attendant economic growth, technological growth, innovation and general Human Resource Development towards National Development. Thus, this article reviewed the literatures on quality administration and management in higher education in Nigeria with the aims of highlighting the implication of human resource development.